Analysis of the Role and Responsibilities of the National Land Agency (BPN) in Resolving Land Boundary Dispute Cases - Wirawan, Rifqi (Sultan Agung Notary Law Review, 2023)
This research aims to analyze: 1) The role of the National Land Agency (BPN) in resolving land boundary dispute cases in Pekalongan Regency. 2) The responsibility of the National Land Agency (BPN) in resolving land boundary dispute cases in Pekalonga Regency. This type of research is descriptive research. The approach method in this research is a sociological juridical approach. This type of data uses primary data and secondary data obtained from interviews and literature studies. The analysis in this research is descriptive qualitative. The results of the research concluded: 1) The role of the National Land Agency (BPN) in resolving cases of land boundary disputes in Pekalongan Regency is as a mediator in resolving these cases. Land disputes in the Pekalongan Regency area which are minor land boundary disputes are generally resolved by both parties to the dispute with mediation and the Pekalongan Regency Land Office acts as mediator. However, it is not uncommon that because the problems are complicated and the disputing parties are difficult to mediate, in the end the settlement is carried out through the courts. However, even in court, the Land Office will still be the party asked for information. 2) The responsibility of the National Land Agency (BPN) in resolving cases of land boundary disputes in Pekalongan Regency, namely that BPN is not only responsible until someone makes administrative efforts, but BPN is given the burden of implementing PTUN decisions related to its main task, namely issuing certificates. . In this regard, certificates that have been canceled by the PTUN which already have legal force must still be followed up in terms of revoking or canceling the certificate. Apart from that, BPN is also responsible for carrying out preventive efforts so that land boundary disputes do not occur. One way is to install land stake boundaries. The installation of land boundary markers is part of the Community Movement for Installing Boundary Marks (Gema Patas) program launched by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN).